Kelas Keberagaman sebagai Pendekatan Edukasi tentang Toleransi bagi Pemuda Kota Malang melalui Agenda Literasi - Wiswayana, Wishnu Mahendra; Yunita, Primadiana (Lembaga Dongan Dosen, 2025)
This community service program focuses on introducing and enhancing tolerance among youth in Malang City through the innovative concept of the Kelas Keberagaman. This approach integrates education and literacy as key tools for promoting an understanding of cultural, religious, and social diversity. The program is designed to address the challenges faced by youth in navigating differences in their daily interactions while fostering empathy, inclusiveness, and mutual respect. Activities in the Kelas Keberagaman include discussions, workshops, storytelling, and creative writing, all aimed at providing participants with practical skills and knowledge on tolerance. By emphasizing literacy as a medium, the program encourages critical thinking and reflection on the value of diversity. The outcomes are expected to empower youth to become active agents of harmony in their communities and to create a foundation for long-term peacebuilding in a multicultural society like Indonesia.